A MCDM approach to the facility location selection problem of sustainable solid waste management - Pınar ÖZKURT (Present Environment and Sustainable Development)
Managing the solid wastes improperly or without sustainability concept will inevitably result in low-grade environmental hygiene and public health, comprising explosion of infectious diseases like malaria, cholera, typhoid/paratyphoid fever, etc. However, managing solid wastes in a sustainable way can reduce both amount of solid wastes and solid waste separation practices. Within this scope, this study concentrates on the establishment of a new sustainable solid waste disposal facility in Türkiye's Mediterranean Region via two effective Multi Criteria Decision Making (MCDM) methods. For this aim, nine criteria; including cost, closeness to residential areas, land slope, environmental risks (e.g., earthquake risk and closeness to water), and public acceptance are utilized through expert evaluations and relevant literature. The most appropriate location is analysed through Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Evaluation based on Distance from Average Solution (EDAS). Both methods consistently determined Yesilyurt Neighborhood in Seyhan District (A1) as the most suitable location for the new solid waste disposal facility. The sensitivity analysis confirmed the robustness of the findings, demonstrating that A1 remained the top-ranked alternative under various criteria weights. It is expected that the results obtained will guide the decision makers in this area.